PENDEKATAN HEUTAGOGI DALAM PENGAJARAN DAN PEMBELAJARAN DI RUMAH (PDPR) MENGGUNAKAN M-PEMBELAJARAN: APPLICATION OF HEUTAGOGY IN HOME-BASED LEARNING USE OF M-LEARNING - Mustafa Kamal, Noor Muslieah; Hussin, Zaharah; Sulaiman, Abdul Muhsien; Abd Latib, Nurul Nadia (Journal of Islamic Educational Research, 2021)
Since 2020, the world of education has seen a shift to a reliance on the use of Information Communication Technology (ICT) to conduct learning activities as a result of the global COVID-19 pandemic. This is aligned with governmental initiatives to integrate technology into the educational system so as to empower and develop a generation of ‘digital natives’ which will be an IT-savvy generation. This study aims to explore the heutagogy approach in teaching and learning Islamic Education using m-learning during pandemic MCO. Seven Islamic Education teachers from secondary school in Selangor have been chosen through purposive sampling technique. Data were collected through semi-structured interviews and document analysis. Data from interviews were transcribed and thematic analysis was used to analyse the interview. The data was then triangulated with document analysis. Findings show that five apps were used by Islamic Education teachers during home-based learning (PdPR) such as YouTube, Google Forms, Google Meet, WhatsApp and Google Classroom. Implementation aspects of heutagogy approach in Islamic Education, the study shows that the role of teachers as facilitators and interactive teaching-activities is very important to improve home-based learning effectiveness.